Anticipated barriers and enablers to signing up for a weight management program after receiving an opportunistic referral from a general practitioner - Chiara Gericke; Sterling Rippy; Danielle D'Lima (Frontiers Media S.A., 2023)
IntroductionGeneral Practitioners (GP) are advised to opportunistically refer patients with overweight or obesity to a tier 2 weight management program, but few patients sign up after receiving the referral. Signing up to a weight management program is a behaviour, as such, behaviour change interventions are needed to increase sign ups. However, no research has explored the influences on signing up after an opportunistic referral specifically.AimTo investigate the influences (i.e., barriers and enablers) on signing up to a tier 2 weight management service after receiving an opportunistic referral from a GP, using a theoretical framework to inform intervention development.MethodSemi-structured interviews were conducted with 18 residents from the London borough of Hounslow who were eligible for the service. Interview guides were informed by the Theoretical Domains Framework (TDF). Data were analyzed inductively using Reflexive Thematic Analysis and Coding Reliability to identify influences on signing up, before being deductively coded to the TDF and grouped into themes.ResultsEight theoretical domains were identified as influences on signing up. Fifteen sub-themes were developed and categorized as either a barrier (5), enabler (3), or mixed (7) influence. Beliefs about Consequences was the most frequently reported influence on signing up. Beliefs that were expressed the most often include how effective the program would be, whether the program is needed to lose weight and whether the program would be compatible with their lifestyle. Leveraging Social Influences and changing patient's Knowledge could address these beliefs and provide a potential route for Behaviour change.DiscussionThe present study provides the first insight into behavioural influences on signing up for a weight management service opportunistically using a validated theoretical framework. This study has implications for intervention development in that public health researchers can identify intervention, content and implementation options based on the findings. Interventions targeting the key domains of Knowledge, Social influences and Beliefs about consequences would likely be the most effective because of their prominence and influence on other domains.